Chapter 7. The Contributions of the ESPGHAN Committees on Nutrition to Paediatric Nutrition. (April 2018) - Hernell, Olle; Aggett, Peter; Fewtrell, Mary; Koletzko, Berthold; Rey, Jean
Abstract : ABSTRACT: The first Committee on Nutrition (CoN) was founded in 1974. Two years later nutrition (N) was added to the society's name, which then became ESPGAN. The Committee systematised compositional and quality criteria for breast milk substitutes and food for special medical purposes, the first of many examples on how recommendations and comments published by the Committees on Nutrition (CsoN) were adopted by the European Economic Community, later the European Union and also influenced the World Health Organization/Food and Agriculture Organization of the United Nations Codex standards. A second CoN focusing on preterm infants was established in 1979 and its recommendations on nutrition of these infants were widely implemented. The third and standing CoN, established 1986, started to organise high-quality symposia at the annual meetings appreciating the need to enhance the expertise in nutritional research. From 1991 the CoN has organised Summer Schools in paediatric nutrition for young colleagues further emphasising its educational interest and more recently an annual, more specialised Nutrition Masterclass. Successively the interest of the CoN has expanded to other areas, such as highlighting dilemmas and uncertainties in the field of nutrition including the design, choice of outcomes and statistical analysis of trials in infant nutrition. The work of the CsoN have had great impact on paediatric nutrition and the committee will continue its important role by writing commentaries and systematic reviews and revising guidelines when required to inform and stimulate discussion among colleagues as well as stimulate training in paediatric nutrition by organising workshops and scientific meetings, training courses, and other approaches, and by interaction with other expert groups.